Thyroid Hormone-Regulated Expression of Period2 Promotes Liver Urate Production - Chen, Xiaoting; Wu, Mian; Liang, Nan; Lu, Junxi; Qu, Shen; Chen, Haibing (Frontiers in Cell and Developmental Biology, 2021)
The relationship between thyroid hormones and serum urate is unclear. Our aim is to analyze the correlation between uric acid and thyroid hormones in gout patients and to explore the effect and mechanism of triiodothyronine on liver uric acid production. Eighty men patients with gout were selected to analyze the correlation between blood urate and thyroid function-related hormone levels. Stepwise multiple linear regression was used to analyze factors affecting blood urate in patients with gout. Levels of urate in serum, liver, and cell culture supernatant were measured after triiodothyronine treatment. Purine levels (adenine, guanine and hypoxanthine) were also measured. Expression levels of Period2 and nucleotide metabolism enzymes were analyzed after triiodothyronine treatment and Period2-shRNA lentivirus transduction. Chromatin immunoprecipitation was used to analyze the effects of triiodothyronine and thyroid hormone receptor-β on Period2 expression. The results showed that in patients free FT3 also influenced the serum urate level. Furthermore, urate levels increased in mouse liver and cell culture supernatant following treatment with triiodothyronine. Purine levels in mouse liver increased, accompanied by upregulation of enzymes involved in nucleotide metabolism. These phenomena were reversed in Period2 knockout mice. Triiodothyronine promoted the binding of thyroid hormone receptor-β to the Period2 promoter and subsequent transcription of Period2. Triiodothyronine also enhanced nuclear expression of Sirt1, which synergistically enhanced Period2 expression. The study demonstrated that triiodothyronine is independently positively correlated with serum urate and liver uric acid production through Period2, providing novel insights into the purine metabolism underlying hyperuricemia/gout pathophysiology.